2001
DOI: 10.1002/path.923
|View full text |Cite
|
Sign up to set email alerts
|

Methylation and colorectal cancer

Abstract: Statistics rate colorectal adenocarcinoma as the most common cause of cancer death on exclusion of smoking-related neoplasia. However, the reported accumulation of genetic lesions over the adenoma to adenocarcinoma sequence cannot wholly account for the neoplastic phenotype. Recently, heritable, epigenetic changes in DNA methylation, in association with a repressive chromatin structure, have been identified as critical determinants of tumour progression. Indeed, the transcriptional silencing of both establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 205 publications
(431 reference statements)
1
93
0
2
Order By: Relevance
“…This signaling, however, only affects CDX1 expression if the CDX1 promoter is either unmethylated or partially methylated, as is expected on the basis that promoter methylation prevents access to regulatory transcription factors (25). We suggest, therefore, that CDX1 promoter demethylation is the key trigger for the development of BM.…”
Section: Discussionmentioning
confidence: 51%
“…This signaling, however, only affects CDX1 expression if the CDX1 promoter is either unmethylated or partially methylated, as is expected on the basis that promoter methylation prevents access to regulatory transcription factors (25). We suggest, therefore, that CDX1 promoter demethylation is the key trigger for the development of BM.…”
Section: Discussionmentioning
confidence: 51%
“…Regional hypermethylation plays an important role in the alteration of gene expression in carcinoma formation and in the progression of carcinoma (Bird, 1996;Jubb et al, 2001;Jones and Baylin, 2002). We found evidence for hypermethylation in the KLF4 5′-UTR in a subset of surgically resected CRC specimens.…”
Section: Discussionmentioning
confidence: 58%
“…The colonic crypt can be considered to consist of a group of clonal cells, because each one of its cells arises from a single stem cell (9,11). It is known that the expression of the cell molecules may be influenced by epigenetic mechanisms during colonic car- (22). Recently, it has been observed that exposure to a non-genotoxic dietrelated compound modulates the chemical carcinogenic effects of nitroso compounds for the induction of crypt-restricted MT immunopositivity (12).…”
Section: Resultsmentioning
confidence: 99%